THE EFFECT OF FREQUENCY OF WATER SUPPLY ON BIOMASS AND GROWTH OF BABY KAILAN (BRASSICA OLERACEAE VAR. ACEPHALA) IN DRIP IRRIGATION SYSTEM - Anggita Mahardika, Rizki
The amount of agricultural land is decreasing in line with the growth of Indonesia's population which continues to increase. The conversion of agricultural land in Indonesia reaches 100,000 hectares per year, which is greater than the government's ability to print agricultural land, which is around 40,000 hectares per year. This conversion of agricultural land has an impact on reducing the rate of food production so that one solution to overcome this problem is to implement an integrated agricultural system. One type of food vegetable whose production needs to be increased is kailan (Brassica oleracea var. acephala), edamame (Glycine max L. Merrill), and cauliflower (Brassica oleracea var. botrytis L.). Cultivation of vegetable crops produces vegetable waste in the form of leaves, stems, and plant roots. Vegetable crop waste is reprocessed into animal feed so that it becomes an integrated farming system. One type of broiler rabbit that can be bred and can consume vegetable waste is the broiler rabbit (Oryctolagus cuniculus) of the New Zealand White race. In addition, rabbit cultivation can meet the needs of meat in Indonesia, which is increasingly increasing with the reduction of meat needs in 2030 as much as 45 kg/capita. Rabbit meat contains high protein and low fat so it is safer from the risk of cholesterol. Rabbit meat contains 20-21% protein, unsaturated fatty acids, calcium, phosphorus, and magnesium, has a low percentage of fat, cholesterol, and sodium. The manure produced by rabbits is used as fertilizer for plant growth. Rabbits also produce urine and manure which can be used as organic fertilizer for plants. Manure and urine from rabbits have higher NPK content of 2.72%N, 1.1%P, and 0.5%K compared to feces and urine from other livestock so that they have the potential to increase plant fertility and productivity. The pre-design of this integrated farming system aims to increase the economic value of cultivating baby kailan, edamame, and cauliflower plants that will be sold to the market, increase the value of plant cultivation by utilizing waste from plant cultivation as animal feed so as to reduce waste, increase the value of economics of rabbits and increase the use value of waste from rabbit livestock as organic fertilizer for plant cultivation or commercialization. The total land area used for this integrated farming system is 1,000 m2 with a land area of 400 m2 for plant cultivation, 80 m2 for rabbit cultivation, 520 m2 for post-harvest areas, warehouse for raw materials and equipment, sewage treatment, water placement, and office . The estimated production capacity is 178.75 kg/year, 29,920 kg/year, 1,664 kg/year. Organic fertilizer from rabbit manure used was 13,083.27 kg/year and POC from rabbit urine was 2,531.15 liters/year. Rabbit production capacity is 518 tails/year or 1,144.78 kg/year. Vegetable waste used as forage feed is 209.63 kg/year. The location used in this integrated farming system is in Cijagra Village, Paseh District, Bandung Regency, West Java, 40383. The location selection is based on environmental conditions for growing conditions for rabbits and plants, availability of raw materials, and access to transportation. The mass and energy balances reviewed in this pre-design include the vegetable cultivation subsystem, the leaf waste utilization subsystem as forage feed, the New Zealand White broiler rabbit cultivation subsystem, and the utilization of feces and urine as organic fertilizer for plants. The vegetable cultivation subsystem consists of 3 units, namely the unit for making fertigation fertilizer solution with a total mass balance of 25,913.73 kJ/year and an energy balance of 57,599.92 kJ/year. Planting media manufacturing unit with a total mass balance of 20,603.6 kJ/year and an energy balance of 177,133,82 kJ/year. Vegetable cultivation unit with a total mass balance of 329,609.08 kJ/year and an energy balance of 225,428 kJ/year. The subsystem of utilizing leaf waste as forage feed has a total mass balance of 4,516.19 kg/year and an energy balance of 33,212.59 kJ/year. The New Zealand White broiler rabbit farming subsystem has a total mass balance of 24,651.28 kg/year and an energy balance of 1,761,995.37 kJ/year. The subsystem for utilizing rabbit manure and urine as organic fertilizer for plants consists of 2 units. The unit processing solid manure into manure with a mass balance of 12,754.29 kg/year and an energy balance of 88,566.91 kJ/year. Unit processing urine into liquid organic fertilizer with a mass balance of 10,970 kg/year and an energy balance of 44,283.46 kJ/year. The initial investment required in the production of this integrated system is Rp192,548,188. The estimated cumulative revenue in the first year is Rp. 414,807,894.3. The income was obtained from the selling price of edamame, baby kailan, broiler cauliflower, rabbit liquid organic fertilizer, and rabbit manure, respectively, at Rp. 15,000/kg, Rp. 63,200/kg, Rp.20,000/kg, and Rp.300. 000/kg, Rp.30,000/liter, and Rp.10,000/kg. Payback Period (PP) is 11 months 4 days since the company started production. The NPV value obtained from this integrated pre-design system is Rp.2.119,948,321. The NPV value shows a positive result (NPV> 0) so that this pre-designed system is feasible to be implemented. The NPV value obtained shows the net profit for the next 10 years according to the current currency value. The payback period (PP) is 11 months and 4 days from the start of the company. The Profitability Index (PI) value shows the profit index obtained by dividing the NPV by the total investment. In addition, a profitability analysis is carried out by determining the value of the Internal Rate of Return (IRR) which shows the company's ability to generate profits expressed in the rate of return (rate of return on capital) which has a zero NPV value. So that the IRR value is 50.08% and the company's Gross Benefit Cost Ratio (Gross B/C) is 2.83. Therefore, the pre-design of this integrated cultivation system is feasible from a financial perspective.